An Overview of Ayushmaan Bharat– Pradhan Mantri Jan Arogya Yojana (International Journal of Food and Nutritional Sciences, 2022)
Ayushman Bharat is National Health Protection Scheme, which will cover over 10 crore poor and vulnerable families (approximately 50 crore beneficiaries) providing coverage upto 5 lakh rupees per family per year for secondary and tertiary care hospitalization. Ayushman Bharat - National Health Protection Mission will subsume the on-going centrally sponsored schemes - Rashtriya Swasthya Bima Yojana (RSBY) and the Senior Citizen Health Insurance Scheme (SCHIS). AB-PMJAY is an entitlement-based scheme. All the eligible beneficiary families are covered from day one of the implementation of the scheme in the States/UTs. AB-PMJAY does not require enrolment. However, beneficiary verification process is being undertaken to verify the genuineness of the beneficiary. Ayushman cards are issued to all eligible beneficiaries as part of this process to ensure easy availing of health benefits.Targets are not fixed for AB-PMJAY as the scheme operates on the basis of beneficiary demand for healthcare services. All the eligible beneficiaries of the implementing States/UTs are entitled for free healthcare services under the scheme from the day of launch of the scheme.While there are significant challenges facing the program, by providing the impetus for system-wide reform, AB-PMJAY presents the nation with a chance to tackle long-term and embedded shortcomings in governance, quality control, and stewardship and to accelerate India’s progress towards the stated goal of universal health coverage provision.